Complexity in social work - Hood, Rick (Sage, 2018)
Complexity lies at the heart of social work practice and this book is designed to help students and newly-qualified social workers plan for and manage complex cases in an increasingly complex environment. Split into two parts, this book reflects the journey of qualifying social work students from preparation for practice in an educational context to learning ‘on the job’ through working with service users in practice settings, and eventually assuming a more senior role in management, administration and training. Key topics covered in the chapters include managing volatility and uncertainty, making judgements and decisions, building and maintaining relationships, using reflection and supervision, working interprofessionally, managing risk, exploring cause and effect.